Have gummosis-free stone fruits - Kumar, Anil; Suyal, Usha; Attri, B. L.; Ahmed, Nazeer; Das, Biswajit; Kishor, Arun (Indian Horticulture, 2019)
Gummosis of peach and plum is an economically important disease in stone fruit-growing areas of Uttarakhand. Its symptom is the formation of cankers accompanied by gum exudation. Gummosis of stone fruits is caused by different biotic and abiotic factors. In Kumaon hills, bacteria (Pseudomonas syringae) has been diagnosed as major pathogen associated with gummosis. This disease can be best managed by procuring certified planting material, removal and destruction of diseased parts, pasting with Bordeaux paste, and spraying with streptocycline (0.01%) plus copper oxychloride (0.2%).